NUMERICAL MODELLING OF THE THERMAL SIGNATURE OF SHIP STACK PLUMES - Bayram, Dundar; Heperkan, Hasan (YILDIZ TECHNICAL UNIV, 2012)
In this article a model has been created for the thermal signature of the ship stack plume gases via computational fluid dynamics and this model was applied to a generated vessel. At the end of this application; ship stack plume density variations, stack plume flow changes, flow speed variations, speed contour and vectoral changes, temperature variations of the exhaust gases and air around the ship, ship surface temperature distribution and cooling distance of the exhaust gases, have been obtained. These results are the main data for calculation of the radiation caused by exhaust plumes and countermeasures against infrared guided missiles.
Keywords: Exhaust gas analysis; thermal signature; compututional fluid dynamics; cooling of the exhaust gases; Engineering